2013
DOI: 10.5792/ksrr.2013.25.4.180
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Revision Using a Modified Articulating Spacer in Infected Total Knee Arthroplasty

Abstract: PurposeTo evaluate clinical results of two-stage revision using a modified articulating spacer for treatment of infected total knee arthroplasty (TKA).Materials and MethodsWe retrospectively reviewed 20 cases treated by two-stage revision arthroplasty using a modified articulating spacer under the diagnosis of infected TKA from January 2006 to December 2011. The mean follow-up period was 22.3 months. The first operation consisted of debridement after removal of the prosthesis, reinsertion of the femoral compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…However, the indications for choosing articulating over static spacers remain unclear. In recent reports, it appears articulating spacers offer comparable rates of infection eradication, improved postoperative flexion, and easier surgical exposure when compared with static spacers, albeit at a higher cost and complexity [3,15,20,23], and it has been noted that restoration of ROM is one of the most critical factors associated with patient satisfaction [18]. Importantly, however, some of the supposed benefits of articulating spacers remain unsubstantiated by the available literature at 2-year and greater followup [5].…”
Section: Discussionmentioning
confidence: 99%
“…However, the indications for choosing articulating over static spacers remain unclear. In recent reports, it appears articulating spacers offer comparable rates of infection eradication, improved postoperative flexion, and easier surgical exposure when compared with static spacers, albeit at a higher cost and complexity [3,15,20,23], and it has been noted that restoration of ROM is one of the most critical factors associated with patient satisfaction [18]. Importantly, however, some of the supposed benefits of articulating spacers remain unsubstantiated by the available literature at 2-year and greater followup [5].…”
Section: Discussionmentioning
confidence: 99%
“…), flash sterilization may be unavoidable . For a number of decades, the procedure of surgically removing an infected total joint device, flash autoclaving and re‐implanting has been practiced …”
Section: Discussionmentioning
confidence: 99%
“…For example, Chen et al observed a 25% rate of recurring infection in patients who were reimplanted with autoclaved femoral components of a total knee system and static spacers, and a 20% rate of recurring infection in patients who were reimplanted with an autoclaved femoral component and received a mobile spacer . Kim et al noted a 10% rate of recurrent infection in patients who were reimplanted with autoclaved femoral components . Qiu et al reimplanted both tibial and femoral components of a total knee system that were autoclaved and saw 10% rate of infection .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described good results with the use of an autoclaved femoral component as an articulating spacer 1718). Compared to an NFC spacer, the autoclaved original femoral component is cost-effective11); however, we are concerned about reusing an implant designed for single use only19).…”
Section: Discussionmentioning
confidence: 99%